2014
DOI: 10.1049/el.2013.3261
|View full text |Cite
|
Sign up to set email alerts
|

Optimising no acknowledgment policy on WLANs supporting voice over internet protocol

Abstract: The efficiency of the no acknowledgment policy, as defined by the IEEE 802.11e amendment, is analysed and an improvement modification to this mechanism is proposed for WLANs supporting voice over internet protocol. Research Committee of the Technological and Educational Institute of Central Macedonia (decision no. 115/14/19613).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Furthermore, it is assumed that data bursts are always available at the transmitting stations. This is not always the case as shown in [9], especially for VoIP applications.…”
Section: Related Workmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, it is assumed that data bursts are always available at the transmitting stations. This is not always the case as shown in [9], especially for VoIP applications.…”
Section: Related Workmentioning
confidence: 93%
“…In our previous work [9], the RTS/CTS was considered as a protection mechanism for the acknowledgment suppression protocol in WLANs supporting voice traffic. In this work it was reported that an efficiency threshold exists under which the NoACK policy is outperformed by the standard DATA/ACK mechanism and a modification to the NoACK protocol was proposed.…”
Section: Related Workmentioning
confidence: 99%